Water Quality Pilot Study for Traditional Water Structure Revitalization Potential in the Deccan Plateau of India - Bessette, Jonathan; Niblock, Eric (Consilience, 2020)
Traditional water structures such as stepwells and canal systems historically function as sustainable water sources. They are advantageous within India’s cyclic climate of flooding and drought, especially in regions of the Deccan plateau. Structures in the Deccan particularly tend to leverage laterite, a porous, geological feature specific to the region. Laterite is especially useful for collecting and maintaining water from surrounding aquifers, permitting reliable storage of water even during the dry season. Unfortunately, many of these structures have been damaged, polluted, and misused. This pilot study investigates the water quality of traditional water structures in the western Deccan Plateau region of India and their potential for revitalization. Samples were drawn from traditional water structures and domestic taps located across Central Maharashtra and Northern Karnataka. Water quality parameters were converted into a single water quality index (WQI) to characterize their current state. Qualitative site information such as degree of conservation and visible pollution level are compared via WQI. Quality amongst some traditional water structures was discovered to be comparable to domestic drinking sources despite a lack of conservation and usage in the former. Some sites exhibited strong potential for revitalization as domestic and agricultural water sources. Finally, a detailed case study of a Karez system in Bidar outlines current characteristics, challenges, and future work in promoting sustainable development practices for revitalizing traditional water structures.